2021
DOI: 10.1016/j.ijpx.2021.100079
|View full text |Cite
|
Sign up to set email alerts
|

Terahertz time-domain spectroscopy for powder compact porosity and pore shape measurements: An error analysis of the anisotropic bruggeman model

Abstract: Terahertz time-domain spectroscopy (THz-TDS) is a novel technique which has been applied for pore structure analysis and porosity measurements. For this, mainly the anisotropic Bruggeman (AB-EMA) model is applied to correlate the effective refractive index ( n eff ) of a tablet and the porosity as well as to evaluate the pore shape based on the depolarisation factor L . This paper investigates possible error sources of the AB-EMA for THz-TDS based tabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…This parameter is investigated by various methods, the most commonly used methods being mercury porosimetry, helium pycnometry, and NMR [51]. In contrast to the aforementioned methods, terahertz techniques and computed tomography allow for imaging of not only open and connected pores in pharmaceutical tablets but also closed ones [52,53]. Moradikouchi et al [54] showed a correlation between porosity measured by the terahertz method and the dissolution rate and disintegration time of ibuprofen and indomethacincontaining formulations.…”
Section: Discussionmentioning
confidence: 99%
“…This parameter is investigated by various methods, the most commonly used methods being mercury porosimetry, helium pycnometry, and NMR [51]. In contrast to the aforementioned methods, terahertz techniques and computed tomography allow for imaging of not only open and connected pores in pharmaceutical tablets but also closed ones [52,53]. Moradikouchi et al [54] showed a correlation between porosity measured by the terahertz method and the dissolution rate and disintegration time of ibuprofen and indomethacincontaining formulations.…”
Section: Discussionmentioning
confidence: 99%
“…The effective medium theory is used to analyze the interaction of the terahertz electric field with the mixture sample, providing hypothetical expressions for calculating the macroscopic dielectric properties of multicomponent composite materials [ 55 ]. The commonly used effective dielectric theory models include the Maxwell Garnett (MG) model [ 56 ], the Bruggeman (BG) model [ 57 ], and the Landau–LifshitZ–Looyenga (LLL) model [ 58 ]. Among them, the BG model and the LLL model are widely used in the field of terahertz bio-detection [ 59 ].…”
Section: Related Technical Theoriesmentioning
confidence: 99%
“…Generally, for immediate release tablets, porosity/pore structure plays a central role in enabling the transport of dissolution liquid in tablets to activate the disintegration process ( Al-Sharabi et al, 2020 ; Dong and Zeitler, 2022 ; Markl et al, 2017a , Markl et al, 2018b , Markl et al, 2020 ; Markl and Zeitler, 2017 ). It has been demonstrated previously that terahertz spectroscopy can be used as a rapid and non-destructive method to measure tablet porosity reliably ( Anuschek et al, 2021 ; Bawuah et al, 2014 , Bawuah et al, 2016 , Bawuah et al, 2020 ; Markl et al, 2017b , Markl et al, 2018a ; Moradikouchi et al, 2022 ). Specifically, THz-TDS is a transmission method to directly measure the total tablet porosity without requiring chemometric analysis and sample preparation ( Bawuah et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%